The Analysis of Value Added Products of Jengkol into J Chips in Padang Village, Manggeng District, Aceh Barat Daya Regency - Hikmah Ruspani; Yoga Nugroho (Britain International for Academic Research (BIAR-Publisher), 2021)
Processing dogfruit into dogfruit chips is one of the potential products to be developed. This study aims to analyze the added value of dogfruit chips using the Hayami method. There are three variables used in this method, namely (1) Output input and price; (2) Revenue and profit and (3) Margin. From the results of the analysis of the production of dogfruit chips, using 10 kg of dogfruit as raw material which produces 7 kg of jengkol chips. The input price for raw material for dogfruit chips, namely dogfruit and edible oil, is Rp. 15,000 per production cycle. The added value obtained is Rp.14,000/kg with the production of 7 kg of dogfruit chips in one production process. Value added ratio 60%.